Research on the potential of some sweet sorghum genotypes as bioethanol source under Mediterranean conditions - Yücel, Celal; Yücel, Derya; Hatipoğlu, Rüştü; Dweikat, İsmail (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2022)
Sweet sorghum (Sorghum bicolor var. saccharatum (L.) Mohlenbr.) is a variety of sorghum developed for the harvest of sweet juice, rather than grain. It has been identified as a potential ethanol feedstock crop for rainfed areas in different parts of the world. It is a promising source of bioenergy due to its high biomass, drought tolerance and low input. This study was conducted to determine the potential of bioethanol production from different sweet sorghum varieties under the Çukurova conditions with a Mediterranean climate. Experiments were conducted over two years in 2016 and 2017 on the experimental fields of the Eastern Mediterranean Agricultural Research Institute in Adana province between June and October in randomized blocks design with four replications. Harvest was performed at the dough stage of panicle grains. Based on two-year data, an average of days to harvest values of the varieties varied between 98.6 and 134.4 days, plant height between 233.2 and 429.3 cm, stalk diameters between 22.26 and 26.55 mm, stalk yields between 69.0 and 182.6 t ha–1, juice yields between 22.98 and 62.74 m3 ha–1, juice recoveries between 26.79% and 39.94%, brix values between 12.55% and 20.0% and theoretical bioethanol yields between 2020 and 5302 L ha–1. Grass1, M81E, Roma, Theis, UNL Hybrid#3 and No91 genotypes had stalk yields over 150 t ha–1 and bioethanol yields over 4500 L ha–1, thus they were superior to the other varieties in stalk and bioethanol yields. Present findings revealed that the Çukurova region was quite suitable for maximum bioethanol production from sweet sorghum.
Keywords: Brix, genotype; stalk and bioethanol yield; sweet sorghum